2007
DOI: 10.1002/esp.1617
|View full text |Cite
|
Sign up to set email alerts
|

Weathering of granite in Antarctica: II. Thermal stress at the grain scale

Abstract: Granular disintegration has long been recognized and referred to in weathering texts from all environments, including the Antarctic. Despite this universal identification and referral, few to no data exist regarding thermal conditions at this scale and causative mechanisms remain little more than conjecture. Here, as part of a larger weathering study, thermal data of individual grains (using infrared thermometry and ultra‐fine thermocouples) composing a coarse granite, as well as the thermal gradients in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…These differences between the 0.5 mm and 1 mm depths are likely related to a combination of heating from the air (having a greater effect at the rock surface) combined with heat due to the solar radiation, and its associated penetration affecting temperature at depth, changing as the angle of the sun to the rock alters through the morning as the sun rises. With both radiative and conductive heat loss from the surface, the 0.5 mm and 1 mm depths become warmer (due to heat being conducted to them from within the rock) than the surface, a not unusual situation (see Hall, Guglielmin, & Strini, 2008b). Although the situation is complex, due to heat gain and loss from both radiative input and internal conduction, complicated by albedo and internal reflection and refraction among the sandstone grains, the impact of radiation-induced simultaneous warming at the surface and at depth can be seen in the insert of Figure 6b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences between the 0.5 mm and 1 mm depths are likely related to a combination of heating from the air (having a greater effect at the rock surface) combined with heat due to the solar radiation, and its associated penetration affecting temperature at depth, changing as the angle of the sun to the rock alters through the morning as the sun rises. With both radiative and conductive heat loss from the surface, the 0.5 mm and 1 mm depths become warmer (due to heat being conducted to them from within the rock) than the surface, a not unusual situation (see Hall, Guglielmin, & Strini, 2008b). Although the situation is complex, due to heat gain and loss from both radiative input and internal conduction, complicated by albedo and internal reflection and refraction among the sandstone grains, the impact of radiation-induced simultaneous warming at the surface and at depth can be seen in the insert of Figure 6b.…”
Section: Resultsmentioning
confidence: 99%
“…Scattering generates an unquantifiable variation to the (linear) vertical transmission of light (and subsequent transfer to heat), it being unquantifiable, as every situation is unique owing to the composition, size, and orientation of crystals. A complication to all of this is the albedo of the rock and its components (see Hall, Guglielmin, & Strini, 2008b, for a discussion), as albedo is not constant but varies daily with the angle of the sun to the receiving surface (Oke, 1999) and changes through the year with the seasons. As Díez-Herrero et al (2009) have clearly demonstrated, solar insolation is a significant factor in causing the degradation of rock art, but its monitoring and evaluation are both complex and difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have addressed roughness quantification specifically and their observations have revealed that rock surface roughness increases (at high rates) after just 4-6 months of exposure, with RMS values initially 14-32 µm and up to 396-492 µm (Fornós et al, 2011). As with the study by Hall et al (2008), these researchers found that surface roughness is affected by widening spaces between rock grains (so, at the grain scale) and their detachment (again, granular disintegration). Finally, X-ray computed tomography was employed (also along with SEM, as by Fornós et al (2011)) in research examining fracture geometry (Ellis et al, 2011).…”
Section: Introductionmentioning
confidence: 83%
“…A reduced contrast would be expected on surfaces with these orientations and this could be affecting the spatial trends. It is evident, for instance, from This could be a product of microclimate and/or associated plant growth, with temperatures on a northfacing exposure experiencing less thermal stress than all other aspects (Hall et al, 2008). Thermal stress indicates that heating-cooling is affecting the wall and this is evident particularly on the west-facing border wall (in comparison to the north-facing wall).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation